Using Direct Reading Thinking Activity (DRTA)Technique to Teach Reading Comprehension for Eleventh Grade Students - Sarona Maisarah; Saiful Akmal; Yuni Setianingsih (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2023)
This research is using the Direct Reading Thinking Activity (DRTA) Technique to Teach Reading Comprehension for Eleventh Grade Students. The research problems of this research are how the use of the Direct Reading Thinking Activity (DRTA) technique may increase reading comprehension for eleventh grade students and what are the obstacles of the students in using the Direct Reading Thinking Activity (DRTA) technique in reading comprehension. The purposes of this research are to find out whether the Direct Reading Thinking Activity (DRTA) technique may increase reading comprehension for eleventh grade students and to know the obstacles the students face in using the Direct Reading Thinking Activity (DRTA) technique in reading comprehension. The subject of this research was the students of the second grade of SMAN 1 Kuta Baro in the academic year 2017-2018, which consisted of 18 students. The research was started on October 10th, 2017 and continued until October 24th, 2017. This is quantitative research with two research instruments, namely a test (pre- and post-test) and a questionnaire. Finally, the researcher concludes by suggesting that English teachers can use the DRTA technique as a good alternative method for teaching reading. However, it aids students' reading ability and comprehension by making texts easier to understand, making students more interactive, and encouraging students to engage in more active and critical thinking.